Use of a nested numerical scheme in a shallow water model for the coast of Bangladesh - Roy, G D; Kabir, A B M Humayun (BRAC University, 2011)
The coast of Bangladesh is very irregular in shape and the off-shore region is full of small and big islands. In this paper a nested finite difference scheme is used to solve the vertically integrated shallow water equations. A fine mesh numerical scheme for the coastal belt of Bangladesh has been nested into a coarse mesh scheme covering up to 15 degree north of the Bay of Bengal. The fine mesh scheme incorporates the off-shore islands and bending of the coastline accurately. The coarse mesh scheme is completely independent and along the open boundaries of the fine mesh scheme, the parameters are prescribed from those obtained in the coarse mesh one in each time step of the solution process. The model is applied to estimate the water level due to tide and surge along the coast of Bangladesh and the results are found to be satisfactory.